Safeguarding the Virtual Realm: Exploring Measures to Address Security and Privacy Concerns in the Rapid Growth of Telecommunication Networks - Joe Laksamana Silitonga (Geviva Edukasi Trans Teknologi, 2023)
This research addresses the pivotal role of societal perceptions in influencing the acceptance and effectiveness of CCTV surveillance for enhancing public safety. The study aims to answer the research question: How do public attitudes shape the efficacy of CCTV systems in promoting public safety and security? The research investigates the complex relationship between public sentiment and the practical outcomes of CCTV surveillance. It delves into the challenges and opportunities arising from varying societal attitudes towards the deployment of surveillance technologies in public spaces. A mixed-methods approach will be employed, combining quantitative surveys to gauge public perceptions and qualitative interviews to capture nuanced views. The research will collect data from diverse demographics to ensure a comprehensive understanding of how different societal groups perceive and respond to CCTV surveillance. This research contributes to the existing literature by offering a nuanced exploration of the impact of societal attitudes on the effectiveness of CCTV systems. The findings aim to inform policymakers, urban planners, and security professionals on the importance of aligning surveillance strategies with public expectations, ultimately enhancing the overall success of public safety initiatives. The mixed-methods approach provides a robust and comprehensive analysis, enriching the understanding of the intricate interplay between societal perceptions and the practical outcomes of CCTV surveillance